POTTERY FROM SCHEDIA NEAR ALEXANDRIA (EGYPT) - Martin, Archer (Rei Cretariae Romanae Fautorum Acta, 2024)
When Alexandria was founded in 331 BC on a limestone ridge between the Mediterranean and Lake Mareotis, Schedia, built at the same time to the southeast on the then westernmost arm of the Nile, the Canopic branch, represented an element necessary for the existence of the great metropolis. A canal was dug between Schedia and Alexandria to bring fresh water to Alexandria and guarantee it access to the Nile Valley. Goods coming downstream had to be transhipped at Schedia in order to travel along the canal. Schedia is also mentioned as the station for the Nile boats belonging to the praefect of Egypt and as a customs station for goods transported up and down the Nile. For the latter purpose a pontoon bridge (swedÙa) was installed, which gave its name to the place. According to the sources the city had a large garrison, temples and a synagogue. It was also one of the first towns in Egypt to be Christianised, with its own bishop’s seat.